Amir Temur and the Times of the Temuris Mints and Monetary Policy (Zien Journal of Social Sciences and Humanities, 2023)
This article analyzed the monetary policy and coinage system in order to improve economic relations in the country during the period of Amir Temur and the Timurids. Taking into account the territorial boundaries of Amir Temur and the Timurid state, we can imagine the size of the state, and the larger the territory, the more difficult and difficult it is to manage. The importance of mints and the coinmoney system was analyzed comparatively.